Konstruksi Realitas Sosial Terhadap Kenaikan Harga Bahan Bakar Minyak (Kajian Semiotik Terhadap Lirik Lagu “Kritis BBM” Karya Slank) - Barkah Hadamean Harahap (UMSU, 2018)
Problems of research is a Kritis BBM lyrics’ serve as the communication messages which lead to the construction of social reality of rising fuel prices. The focus of this research is denoted problems and connotations of Barthes's perspective in the lyrics of critical social impact of feuel price increases of fuel oil. The research method used was qualitative-descriptive approach.Based on the findings of this study showed in denotative and connotative construction of the social reality of the impact of the rising prices of fuel oil in the lyrics of a Kritis BBM proved based on the use of non-formal language, terminology, punctuation and the story in the lyrics. The form of the construction of social reality that is found is the constructive message describing about the regeneration of the future, the future of education and health, lack of well-being on the poor, the hegemony of social criticism, the concept of simple living, government policies are not transparent, social instability, and aid allocation fund compensation fraud. The existence of the social form of reality shows that the song's lyrics aim to change opinions, under the solicitation and change the attitude and behavior of audiencess.